ANALISIS REALISASI ANGGARAN BELANJA RUTIN ADMINISTRASI PERKANTORAN PADA KABUPATEN KUBU RAYA - B51109013, FERDIANSYAH (Jurnal KIAFE, 2013)
This Research entitled "Analysis of Routine Adiministrasi Actual Budget Office in Kubu Raya District", which discusses the problem of effectiveness from the budget that has been realized within a period of one year on units related local government offices in the district of Kubu Raya. The purpose of this study was to determine effectiveness of the implementation of the budget in Kubu Raya District Government and the factors that influence the effectiveness of the level of budget realization. The methods used in this research is descriptive method of data collection techniques such as : interviews, observation, and study of literature. Data analysis tool used was the Minister of Home Affairs No. 13 of 2006, questionnaires and analysis flowchart. From these results it is concluded that the mechanism of the process of implementation of the budget on education Kubu Raya District Government has been going well and according to the Minister of Home Affairs Regulation No. 13 of 2006, where shown on the amount of the budget that has been done effectively realized the above ≥ 75%. However, there is still a realization of its budget on education has not reached effectively, where the rate is still below the realization of < 75%. This shows that in fact there are still several obstacles that led to the realization that the budget can not be fully realized effectively. Keyword : effectiveness, the actual budget, budget execution, systems and procedures.